(untitled) (Colombia Medica, 1992)
Morbidity and mortality of head injury in Cali, Colombia, were analyzed using reference records from the Hospital Universitario del Valle and the clinical Rafael Uribe Uribe, Instituto de Seguros Sociales, from 15 days from November 21 to December 5, 1991. Both institutions received about 90% of head injury in Cali. Only patients from 15 to 65 years old were included. During these 15 days, 209 patients were admitted alive to the emergency rooms, and 55 were sent to the morgue. The majority of the patients were between 20 and 40 years old. Vehicle accidents were responsible for 50% of the cases, violence for 22%, 38% of the patients had consumed alcohol, and 0.5% drugs. If the results of this research are to be compared with studies in San Diego (USA) and Aquitaine (France), the incidence of Cali is twice as high, and mortality is four times higher.